Overexpression of a DUF740 family gene (LOC_Os04g59420) imparts enhanced climate resilience through multiple stress tolerance in rice - Jayaraman, Karikalan; Sevanthi, Amitha Mithra; Raman, Kalappan Venkat; Jiwani, Gitanjali; Solanke, Amolkumar U.; Mandal, Pranab Kumar; Mohapatra, Trilochan (Frontiers in Plant Science, 2023)
Functional characterization of stress responsive genes through the analysis of transgenic plants is a standard approach to comprehend their role in climate resilience and subsequently exploit them for sustainable crop improvement. In this study, we investigated the function of LOC_Os04g59420, a gene of DUF740 family (OsSRDP-Oryza sativa Stress Responsive DUF740 Protein) from rice, which showed upregulation in response to abiotic stress in the available global expression data, but is yet to be functionally characterized. Transgenic plants of the rice OsSRDP gene, driven by a stress-inducible promoter AtRd29A, were developed in the background of cv. Pusa Sugandh 2 (PS2) and their transgene integration and copy number were confirmed by molecular analysis. The three independent homozygous transgenic plants (AtRd29A::OsSRDP rice transformants) showed better resilience to drought, salinity, and cold stresses, but not heat stress, as compared to the non-transformed PS2, which corresponded with their respective relative transcript abundance for OsSRDP. Transgenic plants maintained higher RWC, photosynthetic pigments, and proline accumulation under drought and salinity stresses. Further, they exhibited less accumulation of reactive oxygen species (ROS) than PS2 under drought stress, as seen from the transcript abundance studies of the ROS genes. Under cold stress, OsSRDP transgenic lines illustrated minimal cell membrane injury compared to PS2. Additionally, the transgenic plants showed resistance to a virulent strain of rice blast fungus Magnaporthe oryzae (M. oryzae). The promoter analysis of the gene in N22 and PS2 revealed the presence of multiple abiotic and biotic stress specific motif elements supporting our observation on multiple stress tolerance. Based on bioinformatics studies, we identified four potential candidate interaction partners for LOC_Os04g59420, of which two genes (LOC_Os05g09640 and LOC_Os06g50370) showed co-expression under biotic and drought stress along with OsSRDP. Altogether, our findings established that stress-inducible expression of OsSRDP can significantly enhance tolerance to multiple abiotic stresses and a biotic stress.